Learning models to improve higher-order thinking skills in mathematics: A systematic literature review - Kadarisma, Gida; Dewantara, Jagad Aditya (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2025)
Higher-Order Thinking Skills (HOTS) are essential abilities that students must possess in order to face complex problems and think critically. The role of learning models is crucial in developing students' HOTS, as they provide structured and meaningful learning experiences. Numerous learning models have been applied to facilitate and improve students’ higher-order thinking, particularly in mathematics. This study employed a Systematic Literature Review (SLR) approach, which involved collecting and analyzing previously published articles indexed by Google Scholar. The articles were gathered using the Publish or Perish software, with keywords such as "learning model," "HOTS," and "mathematics." A total of 25 relevant articles were reviewed. The findings revealed that several learning models have proven effective in enhancing students' HOTS, including Problem-Based Learning, Project-Based Learning, Discovery Learning, Creative Problem Solving, CORE, and Missouri Mathematics Program. The specific HOTS skills improved through these models include critical thinking, creative thinking, reasoning, and problem-solving abilities. The implication of this study is that educators are encouraged to design instructional activities using learning models with proven effectiveness in fostering students' higher-order thinking skills.